2018
DOI: 10.1364/oe.26.004686
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the dispersion of effective surface plasmon polaritons with multilayer systems

Abstract: Recently, effective surface plasmon polaritons (ESPPs) induced by structural dispersion in bounded waveguides were theoretically demonstrated and experimentally verified. Despite the theoretical and experimental efforts, whether ESPPs can mimic real SPPs in every aspect still remains an open question. In this work, we go one step further to study the hybridization of ESPPs in multilayer systems. We consider transverse electric (TE) modes in a conventional rectangular waveguide and a parallel-plate waveguide (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…In other words, if two HM SIWs with the same width and different dielectric materials are coupled, in certain frequency range the real parts of the effective dielectric constants of the two would have opposite signs, which would open up a possibility for SPP propagation. This concept, however in parallel-plate waveguide, has been demonstrated in [36,37] and exploited as filter in [38,39] and in multilayer waveguide system [40]. Here, for the first time it is shown how the SPP-like propagation can be achieved in HM SIW and used for sensing applications in microwave regime.…”
Section: Theoretical and Numerical Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…In other words, if two HM SIWs with the same width and different dielectric materials are coupled, in certain frequency range the real parts of the effective dielectric constants of the two would have opposite signs, which would open up a possibility for SPP propagation. This concept, however in parallel-plate waveguide, has been demonstrated in [36,37] and exploited as filter in [38,39] and in multilayer waveguide system [40]. Here, for the first time it is shown how the SPP-like propagation can be achieved in HM SIW and used for sensing applications in microwave regime.…”
Section: Theoretical and Numerical Analysismentioning
confidence: 86%
“…In the case that the two parts are filled with different materials, there is a frequency range in which one part exhibits positive real part of the effective permittivity and the other negative real part of the effective permittivity, allowing for SPP to occur at the I interface. This concept has been applied only in the passive filter [38,39] and multilayer waveguide systems [40], and has never been used for sensing purposes in spite of being very promising for highly sensitive and accurate detection in microwave regime.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method cannot be used to describe the case that the strip is integrated with the dielectric substrate, which is commonly used in real applications. In order to solve this problem, the effective circuit model is introduced to describe the EM behavior of the spoof SPPs from the circuit view [26,[38][39][40][41]. In Refs.…”
Section: Effective Circuit Model Of Spoof Spp Tlsmentioning
confidence: 99%
“…Alternatively, it has been shown that low‐frequency plasmonics can also be realized with structured dispersion in bounded waveguides . Recently, in a couple of scenarios, this approach has been successfully applied to mimic propagating SPPs exhibiting spatial decay on both sides of the interface.…”
Section: Introductionmentioning
confidence: 99%